PENGEMBANGAN PERANGKAT KURIKULUM DAN RANCANGAN PEMBELAJARAN - Sanjaya, Wina; Darmawan, Deni; Supriadie, Didi (PEDAGOGIA, 2014)
Learning success will not be separated from the learning support tool prepared by the educators . in the context of learning tool will typically associated also ideal with irish curriculum and curriculum currents. Curriculum and learning tool singer of which can be include a syllabus , unit class events , learning resources learning or material , as well as learning evaluation. for a review realize all benefits and leading from each - each learning tool singer thus each necessary tools development - development . efforts to develop this is intended to obtain sinergy between each - each device . At the end Of Curriculum And Learning presence of Irish singer then quality learning supported model by , approach , strategy development and methods generate output that can be good .Keywords: Perangkat Kurikulum, Perangkat Pembelajaran.